Experimental Study of Injection Parameters on the Performance of a Diesel Engine with Fischer–Tropsch Fuel Synthesized from Coal - Jinhong Shi; Tie Wang; Zhen Zhao; Tiantian Yang; Zhengwu Zhang (Energies, 2018)
Experimental research was conducted on a turbo-charged, inter-cooling and common-rail diesel engine with Fischer⁻Tropsch fuel synthesized from Coal-to-liquid (CTL), in order to investigate the influence of different injection parameters on the combustion, emissions and efficiency characteristics of the engine. The results showed that the ignition point was advanced, the in-cylinder pressure and heat release rate increased as the injection timing advanced and the injection pressure increased. By comparing the peak in-cylinder pressure of 100 cycles for one sample, it was found that the coefficient variation (COV) remained under 2% throughout the tests and the combustion process remained stable. NOx emissions decreased with delayed injection timing and lower injection pressure. In contrast to NOx emissions, soot emissions were almost zero when the injection pressure was up to 143.5 MPa. The indicated thermal efficiency (ITE) showed no obvious change with different injection parameters, and remained under 40% in all the tests.